Determination of perfluorinated compounds (PFCs) in the fine particulate matter (PM2.5) in China - Billah, Md Baki (Jahangirnagar University Journal of Biological Sciences, 2016)
Perfluorinated chemicals (PFCs) can be absorbed on fine particulate matter (PM2.5) and used as stain, water and grease repellent in a wide range of consumer products. Among the PFCs, perfluorooctane sulfonate (PFOS) and perfluoro octanoic acid (PFOA) are widely detected in human blood and serum and are of concern due to their potential toxicity. In the present experiment, fine particulate matter (PM2.5) from some northern (Beijing, Xian) and southern (Hong Kong, Guangzhou and Xiamen) cities of China were collected and analyzed for perfluoro butanoic acid (PFBA), perfluoro hexanoic acid (PFHxA), perfluoro octanoic acid (PFOA), perfluoro nonanoic acid (PFNA), perfluoro decanoic acid (PFDA), perfluoro undecanoic acid (PFUdA), perfluoro dodecanoic acid (PFDoA), perfluoro hexanesulfonate (PFHxS) and perfluoro octanesulfonate (PFOS) using liquid chromatography mass spectrometry (LC-MS/MS). The total PFCs ranged from 121.2 to 192.2pg/m3, leading by Guangzhou followed by Xian, Beijing, Xiamen and Hong Koung. Among the nine measured PFCs compounds, the level of PFHxS was below the limit of detection in all the sampling cities. The other eight PFCs (PFOS, PFDoA, PFUdA, PFDA, PFNA, PFOA, PFHxA and PFBA) were detected in all the sampling locations except PFDoA in Hong Kong samples. Human exposure estimated to PFCs for adults showed PFOS as the dominant inhaled compound representing 1.59, 1.15, 1.0 and 1.0 ng/day exposure for Hong Kong, Guangzhou, Xiamen, Beijing and Xian respectively. Results from this study contribute to our understanding of exposure pathways of PFCs to humans. Jahangirnagar University J. Biol. Sci. 5(1): 21-27, 2016 (June)